26th AIAA Aerodynamic Measurement Technology and Ground Testing Conference 2008
DOI: 10.2514/6.2008-3943
|View full text |Cite
|
Sign up to set email alerts
|

Description and Flow Assessment of the Delft Hypersonic Ludwieg Tube

Abstract: An assessment of the hypersonic Ludwieg Tube of Delft University of Technology (Hypersonic Test Facility Delft, HTFD) is given. The facility is discussed theoretically and an experimental evaluation is performed to infer the facility performance. Experiments are performed using conventional techniques such as static and total head pressure measurements and Fay-Riddell heat flux evaluations by means of infrared thermography. Furthermore PIV (particle image velocimetry), a more state of the art technique is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The experiments are performed in the Hypersonic Test Facility Delft [27]. The HTFD is a cold hypersonic wind tunnel that operates according to the Ludwieg tube concept that provides Mach 7.5 airflow in a 350 test section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments are performed in the Hypersonic Test Facility Delft [27]. The HTFD is a cold hypersonic wind tunnel that operates according to the Ludwieg tube concept that provides Mach 7.5 airflow in a 350 test section.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore by introducing this delay only the temperature information is used for the period that the tunnel is properly started. As a matter of fact, Schrjier and Bannink [27] showed that stationary flow conditions start approximately 25 ms after the valve opening by measuring the pressure variation in the settling chamber. In figure 1 the comparison between the experimental temperature rise and the heat equation after the introduction of the delay is reported, as can be seen the first 30 ms are neglected.…”
Section: Measurement Techniquementioning
confidence: 99%
“…Sounding rockets are a fast emerging technology giving low-cost access to space [ 1 ]. Sounding rockets also provide important data on aerodynamics at speeds up to hypersonic [ 2 ], which are typically very difficult to achieve in wind tunnels [ 3 , 4 ]. A University of Canterbury Rocketry Research Group [ 5 ] has been formed to develop control systems for high accuracy positioning with a longer term goal of stabilizing rockets through the sound barrier.…”
Section: Introductionmentioning
confidence: 99%
“…A nozzle insert creates a throat area in order to choke the flow, thus preventing flow disturbances from travelling upstream. For this reason, the throat is located upstream of the sealing, as opposite to solutions that are typical in Ludwieg tubes (Schrijer and Bannink 2010;Knauss et al 1999). It can be moved remotely in the longitudinal direction to change the throat area section between approximately 420 and 600 mm 2 , and this allows to modulate the strength of the rarefaction waves.…”
Section: Equipment and Proceduresmentioning
confidence: 99%